The philosophical journey : - Lawhead, William F. (McGraw Hill, 2006)
The Philosophical Journey: An Interactive Approach, 3/e is a text/reader which enhances comprehension of philosophical study by allowing the reader to ponder, explore and actively participate in the learning process. Philosophy becomes a personal journey to students through Bill Lawhead’s innovative and unique pedagogy which delivers philosophical concepts through more digestible chunks. This revised edition includes even greater enhanced pedagogy, updated coverage of the argument for God, terrorism and political theory, updated exercises, readings and more!